Coercive pressure as a moderator on organizational structure and risk management: empirical evidence from Malaysian construction industry - Tagod, Manal; Adeleke, A. Q.; Moshood, Taofeeq D. (Elsevier Ltd, 2021)
Construction industry in Malaysia have been bedevilled by myriads of risk issues which have hampered their smooth operations in recent times. This paper is an empirical assessment that aims to examine the effect of coercive pressure on the relationship between organizational structure and construction risk management among construction companies in Malaysia. Based on the proposed model, a quantitative method was employed to obtain data from G7 construction companies operating in Malaysia Peninsular. Out of the 180 copies of questionnaire, 165 copies were properly filled, returned and used for the analysis. PLS-SEM was used to analyze the obtained data. The findings of the study affirmed that specialization, centralization and management of risk by the construction companies had positive correlation. As anticipated, coercive pressure had positive moderating correlation with both formalization and the management of risk by the construction companies. Similarly, it was also found that in the course of carrying out construction activities, coercive pressure made significant interactive influence on formalization, specialization and centralization. Coercive pressure reduced the frequency of accidents among workers in the process of carrying out construction works.